Analysis of Knowledge and Skills about Breast Care Towards the Following of Breast Milk in Primary Mothers in Ambunten Public Health Center, Sumenep Regency - RA Siti Nurul Farida; Yenny Puspitasari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
The nutritional content of breast milk provides protection for the baby's immune system, so that the baby can grow and develop very well. The purpose of this study is to analyzeinfluence knowledge and skills about breast care for smooth breastfeeding in primiparous mothers at the Ambunten Health Center, Sumenep Regency. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzinginfluence knowledge and skills about breast care for smooth breastfeeding in primiparous mothers at the Ambunten Health Center, Sumenep Regency. The total population of 145 respondents and a sample of 106 respondents were taken using the Simple Random Sampling technique. Data analysis using Linear Regression test. The results of the study show that someMajority of respondents as many as 63 respondents (59%) have knowledge in the category of less. Most of the respondents are not skilled in breast care as many as 73 respondents (69%). Most of the respondents did not experience breast milk dam as many as 57 respondents (54%).Based on the results of Multiple Linear Regression analysis shows that with a p-value of 0.000 <0.05 then H1 is accepted, so it can be concluded that simultaneously there is an influence of knowledge and skills about breast care on the smoothness of breastfeeding in primiparous mothers at the Ambunten Health Center, Sumenep Regency with a magnitude of 75% effect. . It is expected that respondents can carry out breast care independently and routinely to facilitate breastfeeding.